2019
DOI: 10.1016/j.jtho.2019.08.567
|View full text |Cite
|
Sign up to set email alerts
|

MA09.03 Identification of Mechanisms of Acquired Resistance to Poziotinib in EGFR Exon 20 Mutant Non-Small Cell Lung Cancer (NSCLC)

Abstract: period, DL1 was further assessed. 3 (50%) of 6 patients at DL1 experienced a DLT (grade 3 headaches and body pain, grade 3 neutropenia, grade 3 rash, one each). One patient was enrolled at DL -1 and did not have a DLT. The most common treatment-related adverse events (TRAEs) included pleural effusion (n¼9), diarrhea (n¼8), rash (n¼7), AST elevation (n¼6), ALT elevation (n¼6), most of which were grade 1 or 2. 4/4/1 patients had grade 1/2/3 pleural effusion, respectively. 7 (70%) patients had grade 3 TRAEs. No g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“… 38 While insufficient dosing due to toxicity may contribute to short-term responses in patients, early data from the use of poziotinib in EGFR Ex20ins patients suggests rapid acquisition of drug resistance, and the specific mechanisms of resistance have some overlap with those observed to arise in classical mutant EGFR NSCLC treated with approved EGFR inhibitors. 39 Therefore, it is important to consider and anticipate the potential routes of drug resistance in order to achieve durable responses in patients with Ex20ins mutations.…”
Section: Clinical Trial Evaluation Of Ex20ins Targeting Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“… 38 While insufficient dosing due to toxicity may contribute to short-term responses in patients, early data from the use of poziotinib in EGFR Ex20ins patients suggests rapid acquisition of drug resistance, and the specific mechanisms of resistance have some overlap with those observed to arise in classical mutant EGFR NSCLC treated with approved EGFR inhibitors. 39 Therefore, it is important to consider and anticipate the potential routes of drug resistance in order to achieve durable responses in patients with Ex20ins mutations.…”
Section: Clinical Trial Evaluation Of Ex20ins Targeting Agentsmentioning
confidence: 99%
“…Despite having only recently been evaluated in clinical trials, clinical mechanisms of resistance have already been reported for some of the aforementioned Ex20ins TKIs. 39 Here we will outline the currently known resistance mechanisms to poziotinib and other Ex20ins TKIs focusing on on-target mechanisms and compensatory bypass mechanisms of resistance described in the literature ( Figure 2 ). An overview of genomic alterations, mutations, amplifications and copy number losses which are present at baseline or occur at relapse post-TKI treatment in Ex20ins patients are summarized in Table 2 .…”
Section: Known Mechanisms Of Ex20ins Tki Resistancementioning
confidence: 99%
See 3 more Smart Citations